BASIC APPROACHES TO QUALITY MANAGEMENT IN LOCAL GOVERNMENT - Mariekhin S.V., (Pressing Problems of Public Administration, 2016)
Main approaches to quality management in local authorities are considered. Two groups of theseapproaches are de ned. The application of different approaches, their advantages and  aws havebeen thoroughly scrutinized.